A giant teratoma in the anterior mediastinum found prenatally: A case report - Su, Yuntian; Alifu, Ailixiati; Wang, Haifan; Lin, Shibin; Su, Xiaoman; Wei, Yong; Wan, Ying; Chen, Renwei (Frontiers in Pediatrics, 2023)
Prenatal anterior mediastinal teratomas in children are rare. Anterior mediastinal teratoma can cause edema in the perinatal period. Color Doppler ultrasound and chest computed tomography (CT) are of great value in the diagnosis of neonatal anterior mediastinal teratoma. We report a case of a neonatal anterior mediastinal teratoma found prenatally. After birth, the transthoracic echocardiography (TTE) and chest-enhanced CT showed a huge solid mass in the pericardial cavity. Because of compression on the heart, the tumor was completely removed 1 day after birth, and a cardiopulmonary bypass was performed. The pathological result was immature teratoma (grade I). In a 9-month follow-up, the patient remains in good overall condition and no recurrences were observed.